Selection of Bali Cattle as a Bull in Nusa Penida Island-Bali Based on Its Performance and Breeding Value - Warmadewi, Dewi Ayu; Ardika, I Nyoman; Putra, I Gusti Agung Arta (Journal of Veterinary and Animal Sciences; Vol 2 No 2 (2019)DO - 10.24843/JVAS.2019.v02.i02.p03, 2019)
Selection program applied to improve the animal genetic potential.  This program can be carried out based on the performance and breeding values ??of the economic trait of each individual.  The research was carried out for 5 month (from May until September 2018).  The purpose of this study was to find out the superior Bali bull by determining of chest girth male Bali cattle. This study used purposive random sampling method. The number of male Bali cattle with incisor of I0,I1,I2 used in this study were 147,29,19 heads respectively. Performance test was calculated by formula of BV = h 2 ( Pi – P ) (Hardjosubroto, 1994).  The results showed that the average of chest girth male Bali Cattle for I0, I1 and I2 were 135,65±16,98cm; 159,57±13,75cm and 166,26±19,94cm respectively. Based on the breeding value, male Bali cattle coded BK030 with I1 and BK101 with I2 were recommended as a superior Bali bulls because of  their highest ranking.